Effect of calcination temperature and duration on structural and dielectric properties of CaFeO3-δ - Amina BENATIA; Najwa GOUITAA; Taj-dine LAMCHARFI; Farid ABDI; Mustapha HADDAD (Arabian Journal of Chemistry, 2024)
With its perovskite structure, CaFeO3-δ exhibits intriguing properties. It possesses remarkable dielectric properties that make it an attractive candidate for various technological applications such as capacitors, enhanced signal transmission, and other electronic components. The primary objective of this study is to optimize the dielectric properties of CaFeO3-δ perovskite material. For this purpose, an ideal combination of the duration and temperature of calcination was studied. The calcination conditions were variated, from 600 °C to 1100 °C for the temperature at different durations (4 h and 10 h). The XRD results were refined using the Rietveld refinement, showing a simple orthorhombic crystallographic structure. This structure was found for samples calcined at 900 °C, 1000 °C, and 1100 °C during 4 h and 10 h, according to the observed and calculated patterns (Rp ≤ 5 % - Rwp ≤ 7 %) of these ceramics. The sample calcinated at 1000 °C/4h has the closest χ2 factor to 1 which indicates an optimum crystallinity. the crystallite size goes from 70.8245 nm to 99.1266 nm with the increase of the calcination temperature and duration, this parameter was calculated using the XRD peak broadening analysis and the Scherrer equation. SEM analysis revealed, that high temperature and calcination time led to a larger grain size. Notably, samples calcined at 1100 °C/10 h had a larger particle size of 1.312 μm, confirming the crystallite size evolution determined by XRD. FT-IR and Raman analyses further confirmed the samples purity. Dielectric studies showed that the colossal dielectric constant (ε') reached a maximum of 105 for CaFeO3-δ calcined at 1000 °C for both durations. The lower transition temperature was found for the sample calcined at 1000 °C/10 h with a value of 257 °C. The maximum conductivity of 0.22 S/m at 1 MHz was recorded for the CaFeO3-δ calcined at 1000 °C/10 h. Furthermore, the dielectric constant exhibits relaxational behavior, which can be attributed to the strong correlation between the ferrite conduction mechanism and their dielectric behavior. The dielectric material does not follow the ideal Debye theory, according to Cole-Cole analysis, indicating a distribution of relaxation times instead. These obtained properties make this ceramic (CaFeO3-δ calcined at 1000 °C/10 h) a potential candidate for dielectric and electrical device applications such as batterie and electric capacitors.